Selective Epoxidation of Crude Oleic Acid-Palm Oil with in situ Generated Performic Acid - Jumain Jalil, Mohd; Farhan Mohd Yamin, Aliff; Hua Chang, Siu; Suhada Azmi, Intan; Morad, Norhashimah; Hadi, Abdul (International Journal of Engineering and Technology, 2018)
The potential utility of epoxidized vegetables oil has begun to be realized in industrial application with increasing the concern of research to develop value added products from the available vegetables oil. Epoxidized oleic acid is often regarded as a high value oleochemical due to wide range of industrial applications including cosmetic, lubricants, painting and as chemical precursor. For safety reason epoxidation of oleic acid using peracid formed in situ by reacting a carboxylic acid with concentrated hydrogen peroxide (H2O2) was selected. The aim of this study is to optimize the epoxidation of oleic acid of palm oil. The method was evaluated on different parameters such as oxygen carrier, concentration of catalyst as well as different type of vegetables oil. The optimum relative conversion to oxirane (86%) was achieved for 20 minutes of reaction time. From the findings formic acid is a good oxygen carrier for in situ epoxidation. Epoxidation results were based on complete conversion oxirane, rate of epoxidation and stability of the oxirane. This study shown oleic acid was succeffuly transformed into epoxide and oleic acid derived from palm oil potential raw material for production of sustainable and friendly epoxide.
Keywords: Epoxidation; oleic acid; vegetable oils; palm oil; oxirane content